JURISPRUDENTIAL STUDY OF THEFT OF ALIMONY BY WIFE Ø¯ÙˆØ±Ù‡51 Ø´Ù…Ø§Ø±Ù‡3 Ø³Ø§Ù„1398 - ????? ???, ??? ????; ???? ????, ??? ????? (??? ? ????)
One of the exceptions to Hadd for theft is the theft of husband?s property by wife. A review of the Islamic jurists? statements indicates disagreement among them regarding the limits and scope of this issue. A group of Islamic jurists believe that theft of husband?s property by wife in exchange for alimony is absolutely permitted and may not lead to the Hadd of amputation. Another group maintain that theft by wife is authorized only in case she is in emergent need of alimony and the absoluteness of this opinion necessitates that in case of theft of husband?s property by wife, even if the husband does not fail to pay alimony and such theft is neither in exchange for alimony nor equal to it, while the wife is in need of alimony, the Hadd of theft is not executed on her. A third group believe that in case the husband refrains from paying alimony and the wife steals his property to the amount she needs, or if the stolen property is beyond her need, the extra amount does not reach the limit of Hadd, the punishment for such theft is not Hadd. After the arguments of these three groups are studied and criticized, finally, through analyzing the famous hadith of the Prophet, it is concluded that where the wife appropriates the husband's property in exchange for her alimony and the husband fails to pay alimony, non-execution of Hadd is in accordance with the rule, given the existence of debt and application of retaliation (taghass), and is it is not necessary to refer to the Hind's hadith. However, in case the wife appropriates the husband?s property in exchange for the child?s alimony and the husband fails to pay, given the non-existence of debt and the subject of retaliation (taghass), non-execution of Hadd is not in accordance with the rule.  Therefore, the only source for solving the problem in this case is the Hind's hadith.